The Impossible takes a little longer [videorecording] - Henderson, Anne.; Janes, Barbara ([Montreal] National Film Board of Canada, 1986)
This has been captioned for the hearing impaired. It shows some disabled persons in Canada who are successful in their job.
Editor, Sidonie Kerr.
Keywords: Handicapped -- Canada; Sociology